Estudos de SAR e QSAR para um conjunto de triazolopirimidinas inibidores da enzima diidroorotato desidrogenase de Plasmodium falciparum - Macedo, Karlla Gonçalves de (2014)
Drug discovery and development process requires high investments of both time and money. Strategies for drug design aided by computers, CADD (Computer-Aided Drug Design) have gained prominence over the last decades, in order to minimize the impact of those costs. CADD techniques also allow the exploration of a greater number of biological targets and promising molecules. Malaria is an endemic disease in Africa and in South American caused by the protozoa of the genus Plasmodium. In 2012, 207 million cases and 627,000 deaths were estimated, according to the World Health Organization. The enzyme dihydroorotate dehydrogenase (DHODH) catalyzes the fourth step of the pyrimidine biosynthesis, and consists in a validated target for the design of new antimalarial agents. The aim of this study was to develop structure-activity relationships (SAR) rules and to generate quantitative structure-activity relationships (QSAR) models using a set of triazolopyrimidines described in the literature as inhibitors of DHODH from P. falciparum (PfDHODH). SAR rules were established using methods of clustering, activity cliffs and activity landscapes. In addition, several models of 2D-QSAR and hologram QSAR (HQSAR) were developed and validated. The SAR analyses allowed the understanding of the basic structural requirements for the antimalarial activity of triazolopyrimidines, like alkyl halides substituents on the triazolopimidinic ring, hydrophobic substituents in the para position on the benzene ring, all in agreement with the chemical space inside the active site of the PfDHODH. The HQSAR and 2D-QSAR models showed good statistical parameters and good predictive ability. The HQSAR contour maps were also consistent with the chemical space of the active site of the enzyme. The results of this study could serve as guide for the design of new antimalarials with higher potency.